11 - Book Review: Dimensions of Development with Emphasis on Africa. By Tekeste Negash and Lars Rudebeck, eds. Uppsala, Nordiska Afrikainstutet and Forum for Development Studies, 1995, 279p. - Zeleza, Paul Tiyambe (Africa Development, 1998)
Abstract